2019
DOI: 10.1093/ibd/izz049
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal CD103+CD4+ and CD103+CD8+ T-Cell Subsets in the Gut of Inflammatory Bowel Disease Patients at Diagnosis and During Follow-up

Abstract: Background The integrin CD103 is proposed to be a potential therapeutical target in inflammatory bowel disease (IBD), as it can form a heterodimeric integrin with β7 (Etrolizumab, anti-β7 integrin) on epithelial T cells. Therefore, we aimed to study the frequencies of different intestinal CD103+T-cell subsets, both CD4+ and CD8+, in newly diagnosed, untreated IBD patients at baseline and during follow-up, compared with healthy controls. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…Interestingly, the data of xCell indicated that CD4 + and CD8 + T cell proportions are obviously reduced in the blood, which may be caused by the increased migration of T cells into the gut and/or the exhaustion of T cells. Consistent with FACS data from other literatures [ 61 63 ], our xCell analysis highlight the decrease of CD8 + Tem as a general signature in the blood of CD, which is conventionally considered a cytotoxic cell type to defect the infection of virus. Although little is known about the detail mechanism, these phenomena suggest that the decrease of T cells, especially the CD8 + Tem, in the peripheral blood may be a novel feature for certain CD patients.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the data of xCell indicated that CD4 + and CD8 + T cell proportions are obviously reduced in the blood, which may be caused by the increased migration of T cells into the gut and/or the exhaustion of T cells. Consistent with FACS data from other literatures [ 61 63 ], our xCell analysis highlight the decrease of CD8 + Tem as a general signature in the blood of CD, which is conventionally considered a cytotoxic cell type to defect the infection of virus. Although little is known about the detail mechanism, these phenomena suggest that the decrease of T cells, especially the CD8 + Tem, in the peripheral blood may be a novel feature for certain CD patients.…”
Section: Discussionsupporting
confidence: 90%
“…T‐bet bound within Runx3 loci of in vitro induced CD4 + CD8αα + IELs, promoted Runx3 expression and lead to CD103 upregulation 26 . A shift from a proinflammatory CD4 + CD103 + population towards CD103 − leucocytes occurred during active inflammation 28 . Comparison of newly diagnosed IBD cases and patients in remission showed higher abundance of CD103 − subpopulations in the gut of newly diagnosed individuals.…”
Section: T Cellsmentioning
confidence: 99%
“…Roosenboom and colleagues reported decreased numbers of CD103 + CD4 + and CD103 + CD8 + T cells in active IBD and found a rise of these numbers in the remission phase up to levels comparable with healthy controls. In addition, they observed a lower number of CD103 - T cells in healthy controls and IBD patients in remission in comparison with active CD and UC patients ( 65 ). Importantly, this study was not specifically designed to assess T RM cells.…”
Section: T Rm Cells In Inflammatory Bowel Diseasesmentioning
confidence: 99%